Ecological and spatial variations of legacy and emerging contaminants in white-tailed sea eagles from Germany: Implications for prioritisation and future risk management. (January 2022) - Badry, Alexander; Treu, Gabriele; Gkotsis, Georgios; Nika, Maria-Christina; Alygizakis, Nikiforos; Thomaidis, Nikolaos S.; Voigt, Christian C.; Krone, Oliver
Graphical abstract: Highlights: Wide-scope target screening (>2400 pollutants) in livers of white-tailed sea eagles. Stable isotope values (δ15N/δ13C) were used to determine food web influences. Use of an in silico model to predict PBT properties and unravel exposure mismatches. Medicinal products were most common followed by POPs and plant protection products. The combination of legacy POPs and PFAS may exceed toxicity thresholds. Abstract: The increasing use of chemicals in the European Union (EU) has resulted in environmental emissions and wildlife exposures. For approving a chemical within the EU, producers need to conduct an environmental risk assessment, which typically relies on data generated under laboratory conditions without considering the ecological and landscape context. To address this gap and add information on emerging contaminants and chemical mixtures, we analysed 30 livers of white-tailed sea eagles ( Haliaeetus albicilla ) from northern Germany with high resolution-mass spectrometry coupled to liquid and gas chromatography for the identification of >2400 contaminants. We then modelled the influence of trophic position (δ 15 N), habitat (δ 13 C) and landscape on chemical residues and screened for persistent, bioaccumulative and toxic (PBT) properties using an in silico model to unravel mismatches between predicted PBT properties and observed exposures. Despite having generally low PBT scores, most detected contaminants were medicinal products with oxfendazole and salicylamide being most frequent. Chemicals of the Stockholm Convention such as 4, 4 ′-DDE and PCBs were present in all samples below toxicity thresholds. Among PFAS, especially PFOS showed elevated concentrations compared to other studies. In contrast, PFCA levels were low and increased with δ 15 N, which indicated an increase with preying on piscivorous species. Among plant protection products, spiroxamine and simazine were frequently detected with increasing concentrations in agricultural landscapes. The in silico model has proven to be reliable for predicting PBT properties for most chemicals. However, chemical exposures in apex predators are complex and do not solely rely on intrinsic chemical properties but also on other factors such as ecology and landscape. We therefore recommend that ecological contexts, mixture toxicities, and chemical monitoring data should be more frequently considered in regulatory risk assessments, e.g. in a weight of evidence approach, to trigger risk management measures before adverse effects in individuals or populations start to manifest.